2019
DOI: 10.1111/jace.16889
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening boron carbide through lithium dopant

Abstract: The high strength of boron carbide (B4C) is essential in its engineering applications such as wear‐resistance and body armors. Here, by employing density functional theory simulations, we demonstrated that the strength of B4C can be enhanced by doping lithium to boron‐rich boron carbide (B13C2) to form r‐LiB13C2. The bonding analysis on r‐LiB13C2 indicates that the electron counting rule (or Wade's rule) is satisfied in r‐LiB13C2 whose formula can be written as r‐Li+(B12)2‐(CB+C). The shear deformation on r‐Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
(186 reference statements)
1
14
0
Order By: Relevance
“…An et al showed this to be the case by performing DFT simulations in which the -CBC-chains with microalloying elements such as -Si 2 -. 25,26 This review paper aims to describe and discuss the experimental observations of stress-induced amorphization in multiple generations of boron carbide, which are referred to as several variants. The first variant is the stoichiometric boron carbide with nominal B 4 C composition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An et al showed this to be the case by performing DFT simulations in which the -CBC-chains with microalloying elements such as -Si 2 -. 25,26 This review paper aims to describe and discuss the experimental observations of stress-induced amorphization in multiple generations of boron carbide, which are referred to as several variants. The first variant is the stoichiometric boron carbide with nominal B 4 C composition.…”
Section: Methodsmentioning
confidence: 99%
“…No references were found on modeling of the PIP process for CMCs, though experimental studies on this manufacturing process have been reported. Studies on polycarbosilanederived SiC ceramic 25 and SiC/SiC composite 26,27 have shown that porosity decreases and mechanical properties improve with the increasing number of PIP cycles. Zhu et al 28 show that increasing pyrolysis temperature and the concentration of SiC fillers in polycarbosilane polymer result in improved mechanical properties in two-dimensional Carbon/ SiC (C/SiC) composites fabricated using the PIP process.…”
Section: With Permissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches, such as microalloying, [12][13][14][15][16] stoichiometry control, [17][18][19] and addition of a second phase, [20][21][22] have been proposed to mitigate amorphous shear band formation. For microalloying, both non-metal dopants (P 23 and Si 24 ), as well as metal dopants (Li, 14,15 Mg, 12,16 and Ti 13 ) may decrease amorphization in B 4 C. Both experimental and theoretical studies have suggested that boron enrichment is helpful to mitigate amorphization. [17][18][19] Moreover, the addition of the second phase, such as SiC 25 and TiB 2 26 has been shown to improve the fracture toughness of B 4 C. Among these approaches, grain-boundary (GB) engineering is promising.…”
mentioning
confidence: 99%
“…This suggests that adding Si or P to the grain boundaries might improve ductility. Several approaches, such as microalloying, [12][13][14][15][16] stoichiometry control, [17][18][19] and addition of a second phase, [20][21][22] have been proposed to mitigate amorphous shear band formation. For microalloying, both non-metal dopants (P 23 and Si 24 ), as well as metal dopants (Li, 14,15 Mg, 12,16 and Ti 13 ) may decrease amorphization in B 4 C. Both experimental and theoretical studies have suggested that boron enrichment is helpful to mitigate amorphization.…”
mentioning
confidence: 99%